The production of carbon - carbon composite materials based on carbon nanofibers by the gas - phase method - A. I. Nikolaev (Тонкие химические технологии, 2015)
It is shown that by varying the conditions of pyrolytic carbon coating of carbon nanofibers and activating the resulting carbon composites it is possible to obtain carbon-carbon composite materials with a wide range of characteristics. Mathematical models of processes of pyrolytic carbon coating of the source material and the activation of the obtained composite allow to determine the area of the process.